Entrepreneurship in Post-Conflict Transition : The Role of Informality and Access to Finance - Demirgüç-Kunt, Asli; Klapper, Leora F.; Panos, Georgios A. (2012)
The authors examine the factors affecting the transition to self-employment in Bosnia and Herzegovina, using the World Bank Living Standard Measurement Survey panel household survey for the years 2001-2004. In the beginning of the sample, the country changed its legal framework, with the primary aim to promote labor market flexibility and to encourage entrepreneurial activity. The analysis identifies individuals that switched to self-employment (employers and own account) during the sample period and the viability of this transition, in terms of business survival for more than one year. The results suggest an important role for financing constraints. Specifically, wealthier households are more likely to become entrepreneurs and survive in self-employment. After controlling for household wealth, having an existing bank relationship increases the likelihood of starting a business with hired employees and increases the chances of survival for the new entrepreneur. By contrast, overseas - and in some cases domestic - remittances decrease the likelihood of becoming an entrepreneur.